2021
DOI: 10.1016/j.funbio.2020.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the effect of interacting forecasted abiotic factors on growth and aflatoxin B1 production kinetics by Aspergillus flavus

Abstract: The aim was to decipher the temporal impact of key interacting climate change (CC) abiotic factors of temperature (30 vs 37 °C), water activity (aw; 0.985 vs 0.930) and CO2 exposure (400 vs 1000 ppm) on (a) growth of Aspergillus flavus and effects on (b) gene expression of a structural (aflD)and key regulatory gene (aflR) involved in aflatoxin B1 (AFB1) biosynthesis and (c) AFB1 production on a yeast extract sucrose medium over a period of 10 days. A. flavus grew and produced AFB1 very early with toxin detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Most of the previous work on the resilience of A. flavus strains to climate changerelated abiotic factors has focused on those originating from maize [8,22]. On a conducive defined nutritional medium for toxin production, it was found that growth was unaffected by 650 or 800 ppm CO 2 exposure at 35 • C under freely available or water stress conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the previous work on the resilience of A. flavus strains to climate changerelated abiotic factors has focused on those originating from maize [8,22]. On a conducive defined nutritional medium for toxin production, it was found that growth was unaffected by 650 or 800 ppm CO 2 exposure at 35 • C under freely available or water stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by increased expression of biosynthetic genes involved in AFs production, including an early structural gene (aflD) and a regulatory gene (aflR) in biosynthetic pathway. Indeed, a subsequent kinetic study also showed that this stimulation of AFB 1 occurred when A. flavus was exposed on maize-based media to climate change scenarios [8].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Medina et al [ 3 ] suggested that often while exposure of mycotoxigenic fungi such as A. flavus to interacting climate-related abiotic factors has little effect on growth, this does however result in a significant stimulation of aflatoxin B 1 (AFB 1 ) production on milled maize-based media and in stored maize. Indeed, recent studies have shown that the kinetics of AFB 1 production change over time when this species is exposed to climate-related abiotic factors [ 28 ]. This is supported by relative expression of key structural and regulatory genes involved in the biosynthesis of aflatoxins.…”
Section: Discussionmentioning
confidence: 99%